Mengantisipasi Perubahan Radikal Dalam Perjalanan Seorang Pemimpin Kristen - Tantra Lingga Weinardy; Andre Yulius; Saibun Panjaitan; Antoni Bastian; Daniel Gunarso (Jurnal Teologi dan Pelayanan Kerusso, 2018)
Changes in our Life might not always be detectable, even sometimes the scale of changes can be as radical as we can imagine. This radical changes also happen in every Leader’s Journey of Life whether he or she likes it or not. However, Leaders should learn to accept it or further than that Leaders should anticipate the changes with open minded and ready to adjust his/her leadership style so that he/she can brings the whole team to achieve the goal that have been set for their purpose. Moreover, Leaders must introspects a few points of indicators that can broaden up to his/her personal acceptance upon this radical changes and turn it to his/her advantage to leap and overcome the changes for the sake of his/her life, the organization and his/her fellowmen.